Cubic phase stability, optical and magnetic properties of Cu-stabilized zirconia nanocrystals. (14th May 2018) - Pramanik, Prativa; Singh, Sobhit; Joshi, Deep Chandra; Mallick, Ayan; Pisane, Kelly; Romero, Aldo H; Thota, Subhash; Seehra, M S
Abstract: By means of experimental and ab initio investigations, we report on the cubic phase stability of Cu doped zirconia (ZrO2 ) at room temperature, and further characterize its structural, optical and magnetic properties. Various compositions of Zr1− x Cu x O2 (0.01 ⩽ x ⩽ 0.25) nanocrystallites of average size ̃16 nm were synthesized using co-precipitation technique. Thermal analysis and kinetics of crystallization revealed that the cubic phase at ambient temperature can be stabilized by using a critical calcination temperature of 500 °C for 8 h in air and a critical composition of . For x < x c, some undigested monoclinic phase of ZrO2 exists together with the cubic structure. However, for x > x c, the monoclinic CuO emerges as a secondary phase with shrinkage of unit-cell volume with increasing the Cu content. At x = 0.05 and 500 °C calcination temperature, we observe a high degree of cubic crystallinity which breaks down into monoclinic phase with increasing calcination temperature beyond 550 °C. Electron magnetic resonance studies provide evidence for the substitution of Cu 2+ ( 2 D5/9, 3d 9 ) ions at Zr 4+ sites with g, g and average g a = ( + 2 )/3 ̃ 2.1. The temperature dependence of magnetic susceptibility measurements from 2 K to 300 K exhibits Curie–Weiss behaviour whose analysis using g a = 2.1 and spin S = 1/2 yields x = 0.028 and x = 0.068 for the nominal x = 0.05 and x = 0.20 samples, respectively. This magnetic analysis confirms the findings from x-ray diffraction that only a part of Cu is successfully doped into cubic phase of Cu-doped ZrO2 . The optical bandgap decreases with increasing x, which is due to the emergence of Cu- d states at Fermi-level near the valence bands, thus making Cu-doped zirconia a hole doped ( p -type) semiconductor.